Answer:
if you're simplifying, it should be = -1b - 6
Step-by-step explanation:
1. 4(1-2b) + 7b -10 solve the parenthesis
2. 4 <u>- 8b</u> <u>+ </u><u>7b</u> - 10 combine like(same) terms
3. <u>4</u> - 1b <u>- 10</u> same as 2.
4. -1b - 6
Answer:
Step-by-step explanation:
did u find the answer
<span>Simplifying
2(10 + -13x) = -34x + 60
(10 * 2 + -13x * 2) = -34x + 60
(20 + -26x) = -34x + 60
Reorder the terms:
20 + -26x = 60 + -34x
Solving
20 + -26x = 60 + -34x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '34x' to each side of the equation.
20 + -26x + 34x = 60 + -34x + 34x
Combine like terms: -26x + 34x = 8x
20 + 8x = 60 + -34x + 34x
Combine like terms: -34x + 34x = 0
20 + 8x = 60 + 0
20 + 8x = 60
Add '-20' to each side of the equation.
20 + -20 + 8x = 60 + -20
Combine like terms: 20 + -20 = 0
0 + 8x = 60 + -20
8x = 60 + -20
Combine like terms: 60 + -20 = 40
8x = 40
Divide each side by '8'.
x = 5
Simplifying
x = 5</span>
In my opinion I think that they should use Max's coupon at Charley's Pizza. Hope this helps u!
Answer:
(69)(3)−8
=
15
199≠15
False
Step-by-step explanation:
hope it helps, 69(3) is already bigger than 15, then -8 makes it 199, which is definitely not equal to 15.